COMPUTERIZED SYSTEM THROUGH FRONT OFFICE RECEPTION GUEST - Shinta Sari; Ir. Irwan Nimara (Jurnal Sistem Informasi, 1996)
By using a computerized system tailored to the needs of applications, we get theinformation quickly, which is room service for guests who will stay and transactiondata that had just happened and the easier it can make a report to the leadership.